INVESTIGATION OF CARBON DIOXIDE ABSORPTION CAPACITY AND DISSOLUTION RATE WITH AMINO ACID SALT SOLUTIONS: SODIUM AND POTASSIUM GLYCINATE - İrem Koçyiğit Çapoğlu,; Duygu Uysal,; Özkan Murat Doğan, (Malaysian Journal of Science, 2024)
Global warming is a major world problem and causes climate change. The primary cause of global warming is carbon dioxide (CO2) emissions. Ongoing studies are being conducted to mitigate the effects of this problem. Anthropogenic CO2 emissions occur by burning fossil fuels to generate power and heat. To combat this problem, CO2 must be captured from point emission sources or directly from air. The conventional method to remove CO2 at the point emission sources is post-combustion systems. In these systems, absorption process is generally used to diminish CO2 emission and capturing at the source. Current researches aim to find an efficient and alternative solution to absorption. In this work, sodium glycinate (NaGly) and potassium glycinate (KGly), which are amino acid salt solutions, were investigated for CO2 absorption. Amino acid salt solutions have shown similar absorption kinetics and capacities to amine-based solutions due to same functional group. These solutions are usually more stable to oxidative degradation and have low volatilities, higher surface tensions and the viscosities are very close to waters. Experiments were performed using a stirred cell system at ambient temperature (20°C) and atmospheric pressure (91 kPa), in Ankara, Türkiye. In experiments, sodium glycinate and potassium glycinate concentration was ranged between 0.1 and 1.5 M. The experiments were also repeated with sodium hydroxide and potassium hydroxide in the same concentration range for comparison. In addition, the amino acid salt solutions examined in this study were compared with alkaline solutions and glycine in terms of total CO2 absorption capacity and CO2 dissolution rate. As a result of the experiments, the potassium glycinate solutions gave approximately 1.4 times better results than the sodium glycinate solutions at the highest concentration. Also, functional groups were determined by FTIR analysis of pure and CO2-loaded potassium glycinate solution.